READINESS Of ELEMENTARY SCHOOL TEACHERS IN IMPLEMENTING CHARACTERS INTEGRATED LEARNING IN THE SCIENCE SUBJECT (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
Many problems that arise in today's society are rooted in the issue of morality as a result of the marginalization of the values of character. To solve this problem, need to be enforced the values of good character on every member of the community, and the proper way is through the educational process, including through education in schools ranging from elementary education to higher education. To find out whether the teachers in elementary schools are ready to take this work, the research conducted to determine the readiness of teachers and the problems associated with its implementation. Through a questionnaire calculated in descriptive percentage on a sample of elementary school teachers who are spread in Semarang, Semarang District and Temanggung, it can be concluded that in teachers’ view it is very important to integrate the learning of characters in the lesson. However, they need guidance /examples to develop learning model with its features, which integrate the values of the characters in the science subject.Banyak persoalan yang timbul di masyarakat dewasa ini berakar pada persoalan moralitas sebagai akibat terpinggirkannya nilai-nilai karakter, Untuk mengatasi persoalan ini, perlu ditegakkan lagi nilai nilai karakter yang baik pada setiap anggota masyarakat, dan cara yang tepat adalah melalui proses pendidikan, di antaranya melalui pendidikan di sekolah mulai dari pendidikan dasar sampai pendidikan tinggi. Untuk mengetahui apakah para guru pada Sekolah Dasar siap mengemban tugas ini, maka diadakan penelitian untuk mengetahui kesiapan para guru dan masalah-masalah yang terkait dengan pelaksanaannya. Melalui angket yang kemudian diolah secara deskriptive persentasi pada sampel guru SD yang tersebar di Kota Semarang, Kabupaten Semarang dan Kabupaten Temanggung, dapat diketahui bahwa para guru menganggap sangat penting untuk mengintegrasikan pembelajaran karakter dalam matapelajaran IPA. Namun demikian mereka membutuhkan bimbingan/ contoh untuk mengembangkan model pembelajaran dengan fitur-fiturnya, yang mengintergrasikan nilai-nilai karakter dalam mata pelajaran IPA.